Examiners’ characteristics and attitude toward marking as determinants of knowledge of malpractice indicators (2017)
Examination malpractice has invaded Nigeria and has increased in tempo despite measures intended to curb it. It is therefore not in doubt that some stakeholders and policy makers in the educational sector today including teachers who combine public examining duties may not be knowledgeable enough to track the “menace” while marking. This study, therefore investigated the existing relationship between personal characteristics, attitude toward marking and examiners’ knowledge of examination malpractice indicators. The study is a descriptive research that never manipulated any independent variable but adopted a correlational approach. Four hundred and fifty NECO examiners were drawn using multi - stage sampling technique from nine marking centres in three of the six States of the south west. The two questionnaires used for data collection were Examiners7 Attitude Towards Marking Scale (r = 0.6) and Examiners’ Knowledge of Malpractice Indicators (r = 0.6). The data collected were analysed using multiple regression analysis with alpha level set at 0.05. The study revealed that all the predictor variables had a composite influence on examiners’ knowledge of examination malpractice indicators (R=.355, F8,441=7.957; p<0.05): number of year(s) of marking with NECO (P=-.200), location of marking (P=-.278) and attitude towards marking (P= .157) were found to have significant contribution to examiners’ knowledge of examination malpractice. The findings have implications for examination bodies, examiners and stakeholders in educational sector. It was recommended that there should be intensive training and re-training for all the examiners by the examination bodies where issues related to detection of examination malpractice cases while marking will be discussed. Production of handbook on the indicators of examination malpractice is recommended